2007
DOI: 10.1093/ps/86.5.801
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In Vitro Fermentation and Molecular Microbial Profiles of High-Fiber Feed Substrates Incubated with Chicken Cecal Inocula

Abstract: High fiber and nonstarch polysaccharide-based poultry diets have received more interest recently for retaining or promoting beneficial gastrointestinal microbial populations. The objective of this study was to investigate and compare the in vitro potential fermentability of high-fiber feed substrates (HFFS) by laying hen cecal microflora. Feed sources examined included soybean meal, soybean hull, beet pulp, wheat middlings, ground sorghum, cottonseed meal, 100% alfalfa meal, 90% alfalfa + 10% commercial layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 59 publications
3
61
0
2
Order By: Relevance
“…They reported that adding raw fiber sources had no effect on average daily feed intake from day 1 to day 21 of the age, but it improved the average daily weight gain and feed conversion ratio (FCR). Adding fiber to the diet improves bowel function and development of the digestive system, increases the production of hydrochloric acid (HCl), bile acids and secretion of digestive juices [37], changes the composition and gastrointestinal tract micro flora population of poultry and pig laboratory conditions [38] and breeding conditions [39][40][41]. So, the positive effects of adding fiber on growth performance of broiler chickens is related to the improvement of the digestibility of nutrients and metabolic pathways changes [42].…”
Section: Methodsmentioning
confidence: 99%
“…They reported that adding raw fiber sources had no effect on average daily feed intake from day 1 to day 21 of the age, but it improved the average daily weight gain and feed conversion ratio (FCR). Adding fiber to the diet improves bowel function and development of the digestive system, increases the production of hydrochloric acid (HCl), bile acids and secretion of digestive juices [37], changes the composition and gastrointestinal tract micro flora population of poultry and pig laboratory conditions [38] and breeding conditions [39][40][41]. So, the positive effects of adding fiber on growth performance of broiler chickens is related to the improvement of the digestibility of nutrients and metabolic pathways changes [42].…”
Section: Methodsmentioning
confidence: 99%
“…Ricke hypothesized that the key to limiting S. Enteritidis during molt was to develop low-nutrient dietary strategies, such as formulations with high fiber content, that would still induce molt due to low energy density but were sufficiently fermentable to support an active GIT microflora that would serve as a barrier to pathogen establishment (255). Several molt diets with fermentable substrate combinations have been screened in vitro and shown to support optimal avian cecal fermentation (396)(397)(398) and retain similar cecal microbial molecular profiles (397). In vivo application of some of these diets was shown to retain fermentation and GIT populations during molt while limiting the ability of S. Enteritidis to colonize the GIT and become invasive (255,270,392,399,400).…”
Section: Salmonella Virulence Response and Competition With Git Micromentioning
confidence: 99%
“…It's interesting to note that these treatments correspond to the highest levels of crude fiber and differed by the fiber's quality (raw material profiles). This is in agreement with previous study which showed that fiber's quality (in diet with high levels of fiber) influence bacterial profile (Dunkley et al, 2007). Moreover, Green (1988) postulated that intestinal bacteria may be responsible of degradation of some non-cellulose fraction of the crude fibers in broilers.…”
Section: Analysis Of the Scfas Concentrationssupporting
confidence: 92%